Gambaran Pelaksanaan Oral Hygiene Pada Anak Sekolah Di SDN Gabus 2 Kabupaten Sragen - Wuladari, Febrika; , Siti Arifah, SKp.,M.Kes (2016)
School age is a child at the age of 6-12 years, at this age children's schools into the core experience. Fine and gross motor development increasingly moving towards progress. How to maintain oral health in more detail can be taught to children, so it will cause a sense of responsibility for his own personal hygiene. Oral health problems are the problems faced by vulnerable groups of elementary school age children (SD). The cause of oral health problems including lack of maintaining oral hygiene and teeth as brushing teeth are not right, the habit of brushing your teeth time is not appropriate and the use of toothpaste is not right. Lack of awareness of children for dental hygiene and mouth can cause dental problems and mouth, as also occurred in students SDN Gabus 2 Sragen. This study aims to describe the implementation of oral hygiene among school children in SDN Gabus 2 Sragen. This research is descriptive. Sample of research is 59 students of SDN Gabus 2 Sragen with total sampling technique. Collecting data using questionnaires were analyzed using descriptive analysis test (univariate). Conclusion of the study were (1) The students of SDN Gabus 2 Sragen mostly been brushing their teeth every day only one child only occasional brushing their teeth every day, (2) Students SDN Gabus 2 Sragen in the frequency of brushing teeth 2-3 times a day and there is one student frequency of brushing teeth 1 times a day, (3) when brushing your teeth in the students of SDN Gabus 2 Sragen most that while taking a bath in the morning and evening bath, some students brush their teeth while taking a bath in the morning, afternoon bath and before bed night as many as 12 students and one student while brushing your teeth in the bath in the morning, (4) How to brush his teeth student SDN Gabus 2 is good and true that is rubbing the teeth in the front, side and inside, and (5) students SDN Gabus 2 districts Sragen has a lot when brushing your teeth using toothpaste only one student who sometimes use toothpaste when brushing your teeth.